Transylvanian Hungarians : peasant art (Budapest : Franklin Society Press, 1926)
Bibliotheek Camille Huysmans
Engels
Hongaars
Monografie
Keywords: Volkskunst; folklore; Hongaarse minderheden; Transsylvanië